2012
DOI: 10.1371/journal.pone.0040345
|View full text |Cite
|
Sign up to set email alerts
|

Early Evolution and Historical Biogeography of Fishflies (Megaloptera: Chauliodinae): Implications from a Phylogeny Combining Fossil and Extant Taxa

Abstract: Fishflies (Corydalidae: Chauliodinae) are one of the main groups of the basal holometabolous insect order Megaloptera, with ca. 130 species distributed worldwide. A number of genera from the Southern Hemisphere show remarkably disjunctive distributions and are considered to be the austral remnants or “living fossils” of Gondwana. Hitherto, the evolutionary history of fishflies remains largely unexplored due to limited fossil record and incomplete knowledge of phylogenetic relationships. Here we describe two si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
85
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(95 citation statements)
references
References 47 publications
9
85
0
1
Order By: Relevance
“…† Eosialis and Indosialis ) was introduced by the Indian subcontinent is therefore largely consistent with the Gondwanan origin (more exactly the Indian‐origin) for the Asian endemic Corydalinae and Chauliodinae as proposed by Penny () and Liu et al. ().…”
Section: Discussionsupporting
confidence: 72%
“…† Eosialis and Indosialis ) was introduced by the Indian subcontinent is therefore largely consistent with the Gondwanan origin (more exactly the Indian‐origin) for the Asian endemic Corydalinae and Chauliodinae as proposed by Penny () and Liu et al. ().…”
Section: Discussionsupporting
confidence: 72%
“…The diversification patterns that gave origin to the incredibly diversified fauna of Corydalidae in the Oriental region are of great interest, yet are still poorly understood. Previous studies that attempted to elucidate the diversification of dobsonflies utilized morphology‐based phylogenies to infer their evolution and historical biogeography (Yang & Liu, ; Liu et al ., , , , ). These studies indicated an Indian origin for the Oriental Corydalidae, with northeastern India and adjacent areas, specifically, being the diversification centre for this group.…”
Section: Discussionmentioning
confidence: 99%
“…the Archichauliodes clade and the Protochauliodes clade, as proposed by a recent morphology-based phylogeny of fishflies 4 . Aside from these two clades, the remaining major subgroup of Chauliodinae is the Dysmicohermes clade.…”
Section: Discussionmentioning
confidence: 99%